2022
DOI: 10.1126/sciadv.abj9815
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of a SARS-CoV-2 mRNA vaccine PTX-COVID19-B

Abstract: Safe and effective vaccines are needed to end the COVID-19 pandemic. Here, we report the preclinical development of a lipid nanoparticle–formulated SARS-CoV-2 mRNA vaccine, PTX-COVID19-B. PTX-COVID19-B was chosen among three candidates after the initial mouse vaccination results showed that it elicited the strongest neutralizing antibody response against SARS-CoV-2. Further tests in mice and hamsters indicated that PTX-COVID19-B induced robust humoral and cellular immune responses and completely protected the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 90 publications
(123 reference statements)
5
28
0
Order By: Relevance
“…We observed an approx. tenfold drop of neutralizing titers against the beta variant B.1.351, which has been also reported for mRNA vaccines 45 . The vaccine induced robust mucosal and systemic antibody responses and systemic CD4 and CD8 T-cell responses, when given either in as an intranasal prime/intranasal boost, or as a subcutaneous prime/intranasal boost.…”
Section: Discussionsupporting
confidence: 70%
“…We observed an approx. tenfold drop of neutralizing titers against the beta variant B.1.351, which has been also reported for mRNA vaccines 45 . The vaccine induced robust mucosal and systemic antibody responses and systemic CD4 and CD8 T-cell responses, when given either in as an intranasal prime/intranasal boost, or as a subcutaneous prime/intranasal boost.…”
Section: Discussionsupporting
confidence: 70%
“…MHC-I-restricted epitopes account for the majority, which is consistent with the T-cell response of the Ad5-vectored SARS-CoV-2 vaccine in mice, i.e., that CD8 + T cells dominate the spike-specific response [ 27 ]. This phenomenon was also reported in the ChAdOx1-vectored SARS-CoV-2 vaccine and mRNA vaccines [ 28 , 29 , 30 ]. However, those vaccines elicited a robust CD4 + T-cell response in humans [ 7 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 67%
“…Therapeutics, entered a phase II clinical trial 142 following preclinical testing 143 and a successful phase I trial, which showed that it had a tolerable safety profile at a dose of up to 100 mg among seronegative individuals, and induced high neutralizing antibody levels. In January 2022, a clinical trial was started to compare PTX-COVID19-B with the authorized BNT162b2 COVID-19 vaccine.…”
Section: Reviewmentioning
confidence: 99%